2019
DOI: 10.1016/j.jtho.2019.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Influences the Salutary Effects of Metformin on Survival After Lobectomy for Stage I NSCLC

Abstract: Introduction-Metformin, a common medication used in the treatment of Diabetes Mellitus is known to have anti-cancer effects. We hypothesized that the salutary effect of metformin on the survival of patients with stage I NSCLC is influenced by body mass index (BMI).Methods-Patients undergoing lobectomy for stage I NSCLC without neoadjuvant therapy were included. Univariate and multivariate survival analyses to examine the association between metformin use and overall, disease specific and recurrence free surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 15 publications
4
27
1
Order By: Relevance
“…Our clinical findings are not only in line with the effects of obesity and tumor progression found in many murine lung cancer models but they also reflect the logical outcome of the roundly pro-tumor alterations that obesity triggers in human and murine gene expression (Fig. 2 and Supplementary Tables 4 and 6) and its effects on the immune cell composition of the TME reported by us 65 (Fig. 3) and others.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our clinical findings are not only in line with the effects of obesity and tumor progression found in many murine lung cancer models but they also reflect the logical outcome of the roundly pro-tumor alterations that obesity triggers in human and murine gene expression (Fig. 2 and Supplementary Tables 4 and 6) and its effects on the immune cell composition of the TME reported by us 65 (Fig. 3) and others.…”
Section: Discussionsupporting
confidence: 90%
“…52,63,64 We recently linked metformin use to significantly better survival outcomes specifically in obese patients with early stage lung cancer. 65 It is possible that the contextspecific benefit of this drug may account at least partially for the better lung cancer outcomes found in patients with high BMI.…”
Section: Discussionmentioning
confidence: 99%
“…As an independent prognostic indicator of tumor-related diseases, BMI has got more and more concern by researchers in recent years. BMI was related with the prognosis of breast carcinoma, non-small-cell lung cancer, and so on [20,21]. In this paper, we found that BMI was signi cantly correlated with the prognosis of AEG patients.…”
Section: Discussionmentioning
confidence: 51%
“…Several studies observed favorable treatment outcomes (objective response rate, disease control rate, median progression-free survival, and median overall survival) in patients who received metformin in combination with ICIs without reaching a statistically significant trend ( 1 , 11 , 37 ). The subgroup analysis found a statistically significant association between metformin use and OS in obese patients with a BMI >25 kg/m 2 ; the strength of the association was higher in patients with a BMI >30 kg/m 2 ( 31 ). However, one study found worse treatment outcomes in patients who took metformin plus ICIs with a nonsignificant trend ( 32 ).…”
Section: Metformin Influences the Antitumor Efficiency Of Icismentioning
confidence: 95%
“…In contrast, according to a recently published study, metformin may increase the expression level of PD-L1 in liver kinase B1 (LKB1) wild-type NSCLC via AMPK-LKB1 signaling (71). Moreover, the results of a clinical study showed that metformin use was associated with significantly decreased expression of six (CTLA4, PDCD1, ICOS, BTLA, CD27, and LAG3) of the seven immune checkpoint genes in only those patients who had a high BMI; opposite results were found in the low BMI group (31). The expression levels of four (CTLA4, CD28, BTLA, and CD27) immune checkpoint genes were significantly increased in patients administered metformin.…”
Section: Metformin Exposure Decreases the Expression Levels Of Immune Checkpoint Genesmentioning
confidence: 99%